2012
DOI: 10.1111/cogs.12003
|View full text |Cite
|
Sign up to set email alerts
|

Perhaps Unidimensional Is Not Unidimensional

Abstract: Miller (1956) identified his famous limit of 7 ± 2 items based in part on absolute identification-the ability to identify stimuli that differ on a single physical dimension, such as lines of different length. An important aspect of this limit is its independence from perceptual effects and its application across all stimulus types. Recent research, however, has identified several exceptions. We investigate an explanation for these results that reconciles them with Miller's work. We find support for the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The accumulation process laid out here and shown in Figure 2 can be mimicked by a correlated multiple-accumulator LBA (see Kvam, 2019a, , Figure 8), which can be implemented by a simple neural circuit (Tajima et al, 2019, , supplementary note 3). Certainly, the model can be informed by a better understanding of the similarity relations between the available responses, which may suggest that (for example) edge categories are more distinct or that the underlying construct does not map onto a purely unidimensional representation (Dodds et al, 2012;Kvam & Turner, 2021). Converging evidence from behavioral approaches like multidimensional scaling (Shepard, 1962) and neural similarity measures like representational similarity analysis or neural decoding rates (Kriegeskorte et al, 2008;Raizada & Connolly, 2012) should shed light on better ways to translate physical stimuli into psychological representations that can be incorporated into a model like ours.…”
Section: Figure 15mentioning
confidence: 99%
“…The accumulation process laid out here and shown in Figure 2 can be mimicked by a correlated multiple-accumulator LBA (see Kvam, 2019a, , Figure 8), which can be implemented by a simple neural circuit (Tajima et al, 2019, , supplementary note 3). Certainly, the model can be informed by a better understanding of the similarity relations between the available responses, which may suggest that (for example) edge categories are more distinct or that the underlying construct does not map onto a purely unidimensional representation (Dodds et al, 2012;Kvam & Turner, 2021). Converging evidence from behavioral approaches like multidimensional scaling (Shepard, 1962) and neural similarity measures like representational similarity analysis or neural decoding rates (Kriegeskorte et al, 2008;Raizada & Connolly, 2012) should shed light on better ways to translate physical stimuli into psychological representations that can be incorporated into a model like ours.…”
Section: Figure 15mentioning
confidence: 99%
“…Work byDodds et al (2012) has actually suggested that the ends of some scales may come back around and become more similar to one another, creating a sort of 'ring' shape to the similarity between alternatives. This is easily handled…”
mentioning
confidence: 99%